Effects of Temperature on Photosynthesis and CO(2) Evolution in Light and Darkness by Green Leaves - Hew, Choy-Sin (1969)
Using an open and a closed system of gas analysis, it was found that CO(2) evolution in light and in darkness from plant leaves (sunflower, soybean, watermelon, eggplant, and jackbean) have a different response to temperature. While the rate of CO(2) evolution in light increased with increasing temperature from 17 to 35° and then declined, the rate of CO(2) evolution in darkness increased continuously up to 40°. The rate of CO(2) evolution in light was affected by light intensity. At 1800 ft-c and below 35° the rate of CO(2) evolution in light was greater than in darkness, but above 35° it became lower than in darkness. The Q(10) for CO(2) evolution in light was consistently lower than that in darkness. Apparent photosynthesis decreased with increasing temperature, from 20 to 40° and its rate was affected by both light intensity and oxygen concentration. In leaves of dicotyledonous plants studied the decrease in apparent photosynthesis between 20 to 30° at 21% O(2) was shown to be due primarily to an increase in CO(2) evolution in light with relatively little effect on photosynthesis. In corn which does not evolve CO(2) during illumination there was little effect of increasing temperature on the rate of apparent photosynthesis. The different response to temperature of CO(2) evolution in light and in darkness support the earlier conclusion that these are 2 different processes.